How far are we from vaccination against Helicobacter pylori infection? - David Stubljar; Tomislav Jukic; Alojz Ihan (Taylor & Francis Group, 2018)
Introduction: Helicobacter pylori infection results in chronic gastritis, peptic ulcer, or gastric cancer; therefore, eradication of this bacterium is essential. The strategy for developing effective vaccines against H. pylori entails immunization of mice with a combination of classical and recombinant H. pylori antigens, but this has proven to be onerous in all cases. Areas covered: We have reviewed literature databases in PubMed and Scopus using the key words H. pylori, vaccine, and vaccination and have conducted a systematic review of published clinical trials and animal model studies on vaccines against H. pylori and have tried to summarize why the vaccines are not effective or only partially effective. Expert commentary: This is the perfect time to review vaccine development against H. pylori as, after several failed attempts, promising results were reported by Zeng et al. in 2015. Successful vaccine development requires knowledge of both the immune mechanisms active during natural infection by H. pylori, owing to the complicated host response against the pathogen, and the factors that allow the persistence of bacteria, such as genetic diversity of H. pylori. Moreover, various clinical trials are needed to prove vaccine efficacy.